Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter P - Section P.5 - Factoring Polynomials - Exercise Set - Page 68: 45



Work Step by Step

The given expression can be written as $(x^2)^2-4^2.$ The expression above is a difference of two squares. RECALL: $a^2-b^2=(a-b)(a+b).$ Factor the difference of two squares using the formula above with $a=x^2$ and $b=4$ to obtain $(x^2-4)(x^2+4) \\=(x^2-2^2)(x^2+4).$ Factor the difference of two squares with $a=x$ and $b=2$ to obtain $(x-2)(x+2)(x^2+4).$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.